Modal analysis of the nozzle guide vane in low pressure turbine system of aircraft engine. Issue 1 (February 2021) - Robak, R; Szczepanik, M
Abstract: The aim of the article is to present modal analysis of nozzle guide vane in low pressure turbine system of aircraft engine. Comparison of results obtained by means of finite element analysis with results of experimental one in terms of frequencies and modal forms are presented. Additionally, the article presents consistent results which will be used in further analyses and researches related to the optimization of dynamic characteristics with application of artificial intelligence.